Soil Properties and their Correlations. - Carter, Michael (Wiley, 2016)
An essential guide to improving preliminary geotechnical analysis and design from limited data, 'Soil Properties and their Correlations' provides a summary of commonly-used soil engineering properties and gives a wide range of correlations between the various properties, presented in the context of how they will be used in geotechnical design.